Resolving taxonomic issues of cicadas (Hemiptera: Cicadidae) including new combinations, new synonymies, and revised status, with updates on the diversity of the Brazilian cicada fauna and new records for four South American countries - Sanborn, Allen F. (Zootaxa, 2023)
The taxonomic position and status of historically confused cicada taxa is determined. Species are reassigned based on analysis of type specimens and the application of currently accepted higher taxonomy. Diceroprocta grossa (Fabricius, 1775) is determined to be Megatibicen grossa (Fabricius, 1775) n. comb. with Cicada auletes Germar, 1834 n. syn., Fidicina literata Walker, 1850 n. syn., and Cicada sonora Walker, 1850 n. syn. becoming junior synonyms. Abroma egae (Distant, 1892) is determined to be Brevialavenosa egae (Distant, 1892) n. comb., Abroma temperata (Walker, 1858) is reassigned to become Brevialavenosa temperata (Walker, 1858) n. comb., and Abroma apicifera (Walker, 1850) is determined to be Brevialavenosa apicifera (Walker, 1850) n. comb. Cicada sahlbergi Stål, 1854 is reassigned to become Herrera sahlbergi (Stål, 1854) n. comb. Zammara eximia Erichson, 1848 is reassigned to become Zammaralna eximia (Erichson, 1848) n. comb. Zammara strepens Amyot & Audinet-Serville, 1843 is reassigned to become Orellana strepens (Amyot & Audinet-Serville, 1843) n. comb. Orellana brunneipennis Goding, 1925 is reassigned to become Zammara brunneipennis (Goding, 1925) n. comb. and Orellana pulla Goding, 1925 is reassigned to become Zammara pulla (Goding, 1925) n. comb. Zammara brunneipennis (Goding, 1925) n. comb., n. syn., Zammara pulla (Goding, 1925) n. comb., n. syn., and Zammara erna Schmidt, 1919 n. syn. are made junior synonyms of Zammara intricata Walker, 1850. Orellana pollyae Sanborn, 2011a n. syn. is made a junior synonym of Orellana strepens (Amyot & Audinet-Serville, 1843) n. comb., and Zammara medialinea Sanborn, 2004 n. syn. is made a junior synonym of Zammara luculenta Distant, 1883. Dorisiana brasilianensis Boulard, 2017 n. syn. is determined to be a junior synonym of Dorisiana noriegai Sanborn & Heath, 2014. Two taxa, Carineta viridicollis var. a Stål, 1862 n. syn. and Cicada proponens var. b Walker, 1858c n. syn. are shown to be unavailable as well as junior synonyms of Carineta viridicollis (Germar, 1830) and Parnisa proponens (Walker, 1858c), respectively. Fidicina aldegondae Kulgatz, 1902 (in Kulgatz & Melichar, 1902) rev. stat. is removed from synonymy and reassigned to become Guyalna aldegondae (Kulgatz, 1902 in Kulgatz & Melichar, 1902) rev. stat., n. comb. Cicada costa Dohrn, 1859 is shown to be a misspelling of Cicada casta Stål, 1854 and does not represent a nomen nudum. The alpha diversity of the known Brazilian cicada fauna is now 181 species with new records of Proarna uruguayensis Berg, 1882 and Herrera dentata Sanborn, 2020 and the removal of Diceroprocta grossa (Fabricius, 1775) and Odopoea degiacomii Distant, 1912 from the fauna. New records of Hemisciera maculipennis (de Laporte, 1832) for Bolivia, Guyalna cuta (Walker, 1850) for Paraguay, and Pachypsaltria phaedima Torres, 1960 for Peru are provided.